Improved Nutritional Outcomes and Gastrointestinal Symptoms in Adult Cystic Fibrosis Patients Treated with Elexacaftor/Tezacaftor/Ivacaftor - Stastna, Nela; Kunovsky, Lumir; Svoboda, Michal; Pokojova, Eva; Homola, Lukas; Mala, Miriam; Gracova, Zaneta; Jerabkova, Barbora; Skrickova, Jana; Trna, Jan (Digestive diseases (Basel, Switzerland), 2024)
INTRODUCTION: Cystic fibrosis transmembrane conductance regulator modulator therapy improves nutritional status and quality of life. Clinical trials have shown pancreatic insufficiency conversion, mostly in pediatric patients treated with ivacaftor. Studies with elexacaftor/tezacaftor/ivacaftor (ETI) in older patients have not suggested restoration of exocrine pancreas function, but quality data in adults are lacking. Our aim was to show the effect of ETI in adults with cystic fibrosis (CF) on nutritional status and digestive function. We hypothesized improvement of nutritional parameters and gastrointestinal symptoms, reduction of pancreatic enzyme replacement therapy, but uncertain improvement in exocrine pancreatic function. METHODS: We prospectively enrolled adults with CF treated with ETI from August 2021 to June 2022. We measured anthropometric parameters, laboratory nutritional markers, change of fecal elastase, pancreatic enzymes replacement therapy needs, and gastrointestinal symptoms. RESULTS: In the cohort of 29 patients (mean age 29.1 years), 82.8% suffered exocrine pancreatic insufficiency. After ETI, mean BMI increased by 1.20 kg/m2 (p < 0.001), mean body weight by 3.51 kg (p < 0.001), albumin by 2.81 g/L, and prealbumin by 0.06 (both p < 0.001). Only 1 patient, initially pancreatic insufficient (4.5%, p < 0.001), developed pancreatic sufficiency, indicated by increased fecal elastase from 45 μg/g to 442.1 μg/g. Mean change in lipase substitution decreased by 1,969 units/kg/day (p < 0.001) and stools frequency by 1.18 per day (p < 0.001). CONCLUSION: Our data suggest increased nutritional parameters, lower pancreatic substitution requirements, and improved defecation in adult CF patients on ETI. Improvement in exocrine pancreatic function might be mutation-specific and needs further study.
Keywords: Indoles; chinoliny; Adult; pyrazoly; Male; gastrointestinální nemoci; lidé; pyridiny; Benzodioxoles; chinolony; Treatment Outcome; Quinolones; Humans; Pyrrolidines; Pancreatic Elastase; Quinolines; Exocrine Pancreatic Insufficiency; Elexacaftor/tezacaftor/ivacaftor; Pancreatic enzyme replacement therapy; indoly; Gastrointestinal Diseases; fixní kombinace léků; Cystic Fibrosis; pyrrolidiny; Young Adult; Nutrition; Cystic fibrosis; Nutritional Status; Drug Combinations; benzodioxoly; mužské pohlaví; výsledek terapie; Pyridines; Exocrine pancreas function; Aminophenols; dospělí; mladý dospělý; prospektivní studie; pankreatická elastasa; Pyrazoles; ženské pohlaví; cystická fibróza; nutriční stav; aminofenoly; Female; exokrinní pankreatická insuficience; Prospective Studies